2007
DOI: 10.1523/jneurosci.2923-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Complete Pattern of Ocular Dominance Columns in Human Primary Visual Cortex

Abstract: The occipital lobes were obtained after death from six adult subjects with monocular visual loss. Flat-mounts were processed for cytochrome oxidase (CO) to reveal metabolic activity in the primary (V1) and secondary (V2) visual cortices. Mean V1 surface area was 2643 mm 2 (range, 1986 -3477 mm 2 ). Ocular dominance columns were present in all cases, having a mean width of 863 m. There were 78 -126 column pairs along the V1 perimeter. Human column patterns were highly variable, but in at least one person they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
214
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(242 citation statements)
references
References 69 publications
27
214
1
Order By: Relevance
“…Strong predictions on the layout and scale of columns that should be observed with functional MRI come from extensive studies in non-human primates and in the case of ocular dominance columns, also from human post-mortem samples (Mountcastle 1997, Adams, Sincich et al 2007). Several studies from the Minnesota group have demonstrated the approach for direct measurements of the columnar organization for ocular dominance and orientation (Yacoub, Shmuel et al 2007, Yacoub, Harel et al 2008).…”
Section: High Spatial Resolution Mapping Of Somatosensory Cortexmentioning
confidence: 99%
“…Strong predictions on the layout and scale of columns that should be observed with functional MRI come from extensive studies in non-human primates and in the case of ocular dominance columns, also from human post-mortem samples (Mountcastle 1997, Adams, Sincich et al 2007). Several studies from the Minnesota group have demonstrated the approach for direct measurements of the columnar organization for ocular dominance and orientation (Yacoub, Shmuel et al 2007, Yacoub, Harel et al 2008).…”
Section: High Spatial Resolution Mapping Of Somatosensory Cortexmentioning
confidence: 99%
“…To accomplish this organization, a very intricate mosaic of neurons subserving these computations allows for each computation to be performed over each portion of visual space. These mosaics, including ocular dominance columns, pinwheel orientation columns, and blobs/interblobs have been the subject of much study and argument (e.g., [2,40,41]). It remains to be seen how many maps throughout the visual hierarchy have similarly complex mosaics.…”
Section: Visual Field Maps In Medial Occipital Cortexmentioning
confidence: 99%
“…The search for organizing principles of visual processing in cortex has proven long and fruitful, demonstrating specific types of organization arising on multiple scales (e.g., magnocellular / parvo-cellular pathways [1] and ocular dominance columns [2]). One of the more important larger scale organizing principles of visual cortical organization is the visual field map (VFM): neurons whose visual receptive fields lie next to one another in visual space are located next to one another in cortex, forming one complete representation of contralateral visual space [3].…”
Section: Introductionmentioning
confidence: 99%
“…Blobs are characterized anatomically as zones of increased CO activity in all cortical layers except IVa and IVc of area V1 (Hendrickson et al, 1981;Horton and Hubel, 1981) and most prominent in lower layer II/III. Blobs have been described for some mammalian species, such as the cat (Murphy et al, 1995), and all primates examined so far [e.g., squirrel monkeys (Fitzpatrick et al, 1983;Carroll and WongRiley, 1984), macaques (Horton and Hubel, 1981), and humans (Horton and Hedley-Whyte, 1984;Adams et al, 2007)]. Although there is converging evidence that they are involved in the processing of color, the exact function of blobs remains obscure.…”
Section: Introductionmentioning
confidence: 99%